Karakteritik Kepemimpinan dalam Organisasi Pendidikan Islam - Ava Swastika Fahriana (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2017)
Leadership in Islamic Education Organizations has a central role to educate, guide and encourage all the citizens of schools for the goals and objectives that have been formulated by the school will be realized. Management in the Islamic Education Organization is a process of planning, organizing, directing and supervising the efforts of members of the organization and the use of other organizational resources to achieve predetermined objectives.